Identification of Transcriptional Variation in Aortic Remodeling Using a Murine Transverse Aortic Constriction (TAC) Model - Zhang, Xinlu; Feng, Ting; Zeng, Xin-Xin I.; Liang, Hongbin; Situ, Bo; Zhang, Qiuxia; Zhou, Fengyun; Chen, Yejia; Wang, Tao; Cai, Du; Lin, Xinxin; Xiu, Jiancheng; et al. (Frontiers in Cardiovascular Medicine, 2020)
Arterial remodeling is a major pathological consequence of hypertension, which is rec-ognized as the most common chronic non-communicable disease. However, the de-tailed mechanism of how arterial remodeling induced by hypertension has not been ful-ly elucidated. Evaluating the transcriptional changes in arterial tissue in response to ele-vated blood pressure at the early stage may provide new insights and identify novel therapeutic candidates in preventing arterial remodeling. Here, we used the ascending aorta of transverse aortic constriction (TAC) model to induce arterial remodeling in C57BL/6 male mice. Age-matched mice were subjected to sham surgery as controls. The TAC model was only considered successful if the mice conformed to the criteria (RC/LC blood flow velocity with 5-10 fold change) 1 week after the surgery. Two weeks after surgery, the ascending aorta developed severe remodeling in TAC mice as compared to the sham group. High throughput sequencing was then applied to identify differentially expressed (DE) transcripts. In silicon analysis were then performed to network transcriptional changes systematically. A total of 1019 mRNAs were signifi-cantly changed between TAC and sham group at the transcriptional level. GO (Gene Ontology) and KEGG (Kyoto Encyclopedia of Genes and Genomes) analysis revealed that stress/stimulus/immune-related biological processes played a crucial role during ar-terial remodeling. Our data has provided a comprehensive understanding of global gene expression changes in the TAC model, which suggests that targeting inflammation and vascular smooth cell transformation are potential therapeutic strategies to interfere with the aortic remodeling at the early stage of the hypertension development.